2017
DOI: 10.1007/s10140-017-1479-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings in blunt trauma patients: prevalence, follow-up documentation, and risk factors

Abstract: A large percentage of trauma patients have incidental findings. Therefore, better documentation and follow-up are needed to determine the long-term outcomes of patients with clinically relevant incidental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…No difference was seen in the severity of trauma, age, or length of hospital stay, and although incidental findings were commonly noted in the liver or kidneys, closer examination was often required for incidental findings related to the lungs. Regarding the recognition of incidental findings, James et al . reported that only 12 of 416 trauma patients (1.4%) in whom incidental findings were identified had their incidental findings documented at the time of hospital discharge, whereas Fakler et al .…”
Section: Discussionmentioning
confidence: 99%
“…No difference was seen in the severity of trauma, age, or length of hospital stay, and although incidental findings were commonly noted in the liver or kidneys, closer examination was often required for incidental findings related to the lungs. Regarding the recognition of incidental findings, James et al . reported that only 12 of 416 trauma patients (1.4%) in whom incidental findings were identified had their incidental findings documented at the time of hospital discharge, whereas Fakler et al .…”
Section: Discussionmentioning
confidence: 99%
“…In whole-body CT studies investigating traumatic pathologies due to blunt trauma, the most common incidental chest finding is pulmonary nodules, followed by atherosclerosis [14]. Detection of infection, infiltration, and pleural findings was also very low in other publications [2,15,16].…”
Section: Discussionmentioning
confidence: 96%
“…Comments: None Comments: None respectively [19,65,66,144]. Interpretation should occur three times (immediately using first images, immediately reassessed using the final images and reassessed again by a different radiologist within 24 h) [141,144,146]. ESER endorses abandoning a 'one-size-fits-all-concept' ([63]-p.1142).…”
Section: Discussionmentioning
confidence: 99%